Paraldehyde and methylpentynol and ganglionic transmission - Quilliam, J. P. (1959)
Paraldehyde and methylpentynol blocked transmission of nerve impulses through the superior cervical ganglion of the cat when the drugs were administered intra-arterially to the ganglion or intravenously using the nictitating membrane as an indicator. Electrical studies showed that concentrations of methylpentynol and paraldehyde which blocked transmission in the isolated rat superior cervical ganglion were without action on the preganglionic nerve fibre. In amounts which blocked transmission in the isolated rat ganglion, paraldehyde had no depolarizing activity directly on the ganglion cells and did not interfere with the depolarizing activity of added acetylcholine. The results suggest that the block in transmission of the impulse could be accounted for by a decrease in the release of acetylcholine from the preganglionic nerve terminals. In both species the block was reversible.